Pengetahuan dan Sikap Masyarakat dalam Pencegahan COVID-19 - Emdat Suprayitno; Sylvina Rahmawati; Adivtian Ragayasa; Muchti Yuda Pratama (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2020)
Abstract The World Health Organization (WHO) has declared the 2019 Coronavirus (Covid-19) a global pandemic. This virus is easily transmitted, so it requires knowledge and a good attitude in efforts to prevent transmission. The purpose of this study was to describe the knowledge and attitudes of COVID-19 prevention in the community in Murtajih Village, Pademawu District, Pamekasan Regency. This research is a descriptive study with a cross-sectional non-analytic design. This research uses descriptive analysis with a questionnaire research instrument. The sample of this research is part of the community in the hamlet of East Solo and North Solo, Murtajih Village, Pademawu District, as many as 62 people with a total sampling technique. The results showed that the level of public knowledge in preventing covid-19 in Murtajih Village, Pademawu sub-district was mostly good, as many as 32 people, 51.6%, while the public attitude in preventing Covid-19 in Murtajih Village, Pademawu sub-district was mostly positive as many as 53 people 85, 5%. The results of this study indicate that most of the knowledge of the community in the village of Murtajih, Pademawu district is mostly good and the attitudes are mostly positive. It is hoped that the community will take precautionary measures to prevent transmission of COVID-19 by washing their hands and wearing masks.